Analisis Faktor - Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Pada PT. Indodacin Presisi Utama - Wie Shi Wudjud,; Elidawati, Elidawati; Free Antonius Simanjuntak, (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The purpose of this study is to analyze the influence of top management support, user involvement in system development, training programs and education of user, personal technical ability of information systems on the performance of accounting information systems. This research was conducted at PT. Indodacin Presisi Utamain Medan. The sampling technique used is purposive sampling. The sample of this study was 33 employees and the population of this study was 43 employees at PPT. Indodacin Presisi Utama Data collection is done by distributing questionnaires. Partial test results show that top management support, training programs and education of user and personal technical ability of information systems not have effect on the performance of accounting information systems but user involvement in system development have a effect on the performance of accounting information systems. Simultaneous test shows of top management support, user involvement in system development, training programs and education of user and personal technical ability of information systems together have an influence on the performance of accounting information systems